(untitled) (Scientific journal of the Fergana State University, 2023)
The article presents the results of studying the centers of origin and zoogeographical areas of Lepidoptera insects in the agroecosystem of the Ferghana Valley. In terms of distribution areas, 98 (62%) species of Lepidoptera insects of the study area are distributed in the Palearctic and its subregions.